The Rvg Experience: A Survey of Dentists’ Satisfaction, Challenges, And Recommendations in Western Maharashtra - Patil, Isha; Mahajan, Madhura (Journal of Neonatal Surgery, 2025)
Background - Roentgen's 1895 discovery of X-rays led to the development of digital radiography, including radiovisiography (RVG), which uses digital sensors for capturing detailed dental images. While RVG improves diagnostic accuracy and efficiency, challenges such as technical issues, ergonomic concerns, and the need for better training persist. Dentists' perceptions of RVG, influenced by their experience and comfort with technology, impact patient outcomes. Exploring these experiences can offer valuable insights that could improve the adoption and design of RVG technology. Aims and Objectives - The study aimed to assess dentists' satisfaction, challenges, and recommendations regarding the use of radiovisiography (RVG) technology in clinical practice. Materials and Methodology - This descriptive survey study utilized a questionnaire to gather data. Data was collected via an online survey using Google Forms, involving 198 respondents. The data was analyzed using Microsoft Excel 2007 and StatsDirect software to generate the statistics. Results - The survey revealed a high level of engagement with RVG technology, particularly among early-career professionals, who show a preference for wired systems. While RVG improves diagnostic accuracy and streamlines workflows, challenges such as technical malfunctions and ergonomic concerns remain. Respondents recommended enhancements like AI integration, improved image resolution, and more ergonomic equipment. Conclusion - This survey offers an analysis of the current implementation and use of RVG technology in dental practices. The findings from this survey underscore the transformative impact of RVG on modern dentistry and pave the way for future advancements.